RURAL TOURISM IN THE RAZIM-SINOE AREA - Daniela-Mirela PLEȘOIANU; Violeta SIMIONESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Rural tourism is a form of tourism that takes place in rural areas and has a functional structure of heterogeneous services and housing. Revenues from tourism are permanent and services are offered by staff and specialized. Rural tourism structures are boarding houses, motels, camping sites, holiday camps, creative arts camps, camps for environmental activities, holiday villages. The purpose of this paper is to present and characterize rural tourism in the area Razim-Sinoe terms for shelters and structures catering. We look at the main indicators of tourist traffic: arrivals number, number of overnight stays, average length of stay; the number of foreign tourists arrivals by country of origin; monthly distribution of the number of tourists; arrivals and overnight stays of tourists in accommodation establishments by types of units; occupancy of accommodation establishments. For these aspects we used data provided by National Institute of Statistics,Department of Statistics Tulcea, Strategic Plan for Sustainable Tourism Development in the Danube Delta, developed under the auspices of Tulcea County Council; Master Plan, Danube Delta Biosphere Reserve, developed by Danube Delta National Institute for Research and Development. Data collected were placed in tables and processed to yield graphics that then we have interpreted and analyzed. Thus, after processing the data provided by the authorities, we conclude that it is noted that most of the tourists prefer hotel units, followed by the tourist in the tourist boarding houses and tourist villas; It is obviously an important flow of tourists during the summer and the highest percentages of foreign tourists from countries like Germany (25.4%), Italy (14.14%) and Austria (12.12%). Analyzing the weight of the number of tourists on monday is obviously an important flow during the summer.